PENGARUH KUALITAS PELAYANAN AKADEMIK TERHADAP PENGALAMAN MAHASISWA SERTA IMPLIKASINYA PADA LOYALITAS MAHASISWA DI POLITEKNIK LP3I JAKARTA KAMPUS PASAR MINGGU - Heri Juarsah; Nurjamilah Nurjamilah (JURNAL LENTERA BISNIS, 2026)
The quality of human resources is greatly influenced by the quality of education provided by educational institutions. Teaching quality and academic service quality are important factors in creating positive student experiences and enhancing student loyalty. This study aims to analyze the effect of teaching quality and academic service quality on student experience and its implications for student loyalty at Politeknik LP3I Jakarta, Pasar Minggu Campus.This study employed a quantitative approach with a population of 208 students and a sample of 137 respondents determined using the Slovin formula and selected through random sampling techniques. Data were analyzed using descriptive analysis and path analysis.The results indicate that teaching quality and academic service quality have a positive and significant effect on student experience. However, partially, teaching quality and academic service quality do not have a significant direct effect on student loyalty. Meanwhile, simultaneously, teaching quality, academic service quality, and student experience have a positive and significant effect on student loyalty. These findings suggest that student experience plays an important role in shaping student loyalty toward educational institutions.